Relationship Between Fibrinopeptide A and Fibrinogen/Fibrin Fragment E in Thromboembolism, DIC and Various Non-Thromboembolic Diseases - Mombelli, G; Monotti, R; Haeberli, A; Straub, P W (Thrombosis and Haemostasis, 1987)
Increased fibrinopeptide A (FPA) levels have been reported in various non-thrombotic disorders, including cancer, acute myocardial infarction, liver cirrhosis and collagen vascular diseases. To investigate the significance of these findings, the present study combined the radioimmunoassay of FPA with that of fibrinogen/fibrin degradation fragment E (FgE) in the aforementioned disorders and compared the results with those observed in healthy subjects as well as in patients with thromboembolism and overt disseminated intravascular coagulation (DIC). Mean FPA and FgE in malignancy were 6.3 and 305 ng/ml, in myocardial infarction 5.6 and 98 ng/ml, in liver cirrhosis 2.7 and 132 ng/ml and in collagen vascular diseases 5.6 and 142 ng/ml. All these values were significantly higher than in healthy controls (mean FPA 1.6 ng/ml, mean FgE 49 ng/ml) but significantly lower than in thromboembolism (mean FPA 10.7 ng/ml, mean FgE 639 ng/ ml) and DIC (mean FPA 22.0 ng/ml, mean FgE 1041 ng/ml). The overall correlation between FPA and FgE was highly significant. Elowever, different disorders showed peculiar patterns in FPA, FgE and fibrinogen levels. In malignancy, a definite increase of FPA, FgE and plasma fibrinogen levels was observed. This finding probably indicates a compensated state of (intra- or extravascular) fibrin formation and lysis. Acute myocardial infarction was characterized by a high FPA to FgE ratio, which is interpreted to reflect acute thrombin generation and fibrin formation. FPA in cirrhosis was only marginally elevated with most single values within the normal range, indicating that intravascular coagulation was infrequent and unimportant in quantitative terms.
Keywords: Fibrinopeptide A; Fibrinogen/fibrin fragment E; Low-grade DIC